1996
DOI: 10.1037/0022-006x.64.1.179
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an outpatient intervention targeting suicidal young adults: Preliminary results.

Abstract: This study evaluated the effectiveness of a time-limited, outpatient intervention targeting suicidal young adults. Participants (N = 264) were randomly assigned to either the experimental treatment or the control condition (i.e., treatment as usual). In addition to intake assessments, participants completed follow-ups at 1, 6, 12, 18, and 24 months. Both treatment and control participants evidenced significant improvement across all outcome measures throughout the follow-up period. Reductions were reported in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
146
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(155 citation statements)
references
References 52 publications
8
146
0
1
Order By: Relevance
“…This study also supports the results of Rudd et al, (1996), whereby ICBT were shown to be effective in treatment of depressive symptoms with suicidal ideation. Since this clinical trial was done among three major ethnic groups in Malaysia, it has additional contribution to the growing literature examining the treatment of depression and also suicidal behavior on Eastern ethnic and cultural groups since group cognitive behavior therapy was reported to be effective in the treatment of depression among Malay patients in Malaysia .…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…This study also supports the results of Rudd et al, (1996), whereby ICBT were shown to be effective in treatment of depressive symptoms with suicidal ideation. Since this clinical trial was done among three major ethnic groups in Malaysia, it has additional contribution to the growing literature examining the treatment of depression and also suicidal behavior on Eastern ethnic and cultural groups since group cognitive behavior therapy was reported to be effective in the treatment of depression among Malay patients in Malaysia .…”
Section: Discussionsupporting
confidence: 79%
“…The findings of current study on improvement of suicide ideation symptoms using the ICBT, are consistent with previous findings (Rudd et al, 1996;Stanley et al, 2009), whereby ICBT reduces suicidal behavior among patients with suicide ideation. According to Brown et al, 2005, the usage of ICBT approach in preventing suicidal behavior can also significantly lower on measure of depressed mood and hopelessness.…”
Section: Measures Of Suicide Ideation Symptomssupporting
confidence: 81%
See 2 more Smart Citations
“…The Suicide Probability Scale was included as it is a recognized predictor of suicide risk (e.g., Larzelere et al, 1996;Witte et al, 2005) and it has been shown to be sensitive to changes in suicidality (e.g., Rudd et al, 1996). To maximize follow-up, we made concerted efforts to contact all participants via post, email and telephone.…”
Section: Participants and Proceduresmentioning
confidence: 99%